Antibacterial and Anti-biofilm- Forming Activity of Secondary Metabolites from Sansevieria trifasciata- Leaves Against Pseudomonas aeruginosa - Dewatisari, Whika; Nugroho, Laurentius Hartanto; Retnaningrum, Endah; urwestri, Yekti Asih P (Indonesian Journal of Pharmacy, 2022)
Sansevieria trifasciata is a herbaceous plant frequently used in traditional medicine with antibacterial potency against Pseudomonas aeruginosa. P. aeruginosa is a known bacterial pathogen that often becomes resistant to traditional antibiotics due to its ability to form biofilms. The objective of this research was to determine whether the ethanolic extract of S. trifasciata has any antibacterial or anti-biofilm-forming activity against P. aeruginosa. Bacterial cell damage with a potential fraction of S. trifasciata ethanolic extract treatment was observed by scanning electron microscopy (SEM). An Anti-biofilm assay was perfomed in 96 wells with crystal violet stain. The minimum inhibitory concentration (MIC) results revealed that at a concentration of 4 mg/mL, the potential fraction of S. trifasciata ethanolic could inhibit bacterial growth. At this concentration, the potential fraction of S. trifasciata ethanolic extract could inhibit the biofilm by 60%. The identification of compounds using gas chromatography-Mass Spectrometry (GC-MS) revealed that Neophytadiene was the main active component in the extract. These compounds have the potential to be used as therapeutic agents in the prevention of bacterial biofilms and virulence-related infectious illnesses